Anisotropy of Magnetic Susceptibility and Elemental Compositions in Andesitic Rocks - Khumaedi Sastrawiharja; Satria Bijaksana; Umar Fauzi; Linus Ampang Pasasa (Institut Teknologi Bandung, 2008)
Igneous rocks, including andesites, are composed of these major elements: Si, Ti, Al, Fe, Mn, Ca, Mg, Na, K, and P. Variation in the composition of these elements, which occur mostly as oxides, determines the overall physical properties of the rocks. Not surprisingly, classification of igneous rocks is also based on the quantity of these major oxides. In this study, elemental compositions of andesitic rocks from the Island of Java will be compared to the anisotropy of magnetic susceptibility (AMS) as a part of our effort to explore the possibility of using rock magnetic parameters in classifying igneous rocks. The objective is to check whether AMS parameters could serve as alternative to chemical analysis. To do so, we have measured the AMS and geochemical composition of andesitic rock samples from 10 different sites across Central Java and Yogyakarta. The results show that there are significant correlations between the abundance of certain elements with AMS parameters, for example, the abundance of Fe and Al with magnetic lineation and the abundance of Al with degree of anisotropy. These results show that magnetic parameters have a good change to be use as predictors for major elements composition in igneous rocks.